Network distribution of molybdenum among pure titanium powders for enhanced wear properties. Issue 1 (January 2021) - Yamanoglu, Ridvan
Abstract : A homogeneous network distribution of molybdenum particles among pure titanium particles was successfully produced by powder metallurgy. The Ti– x Mo mixtures were consolidated by uniaxial hot pressing under a 10 −4 mbar vacuum atmosphere at 950 °C for 30 min. The distribution of the molybdenum particles in the structure was investigated by optical and scanning electron microscopy in polished and etched conditions. The dry sliding wear properties of the Ti– x Mo compacts and the Ti6Al4V alloy was carried out using a ball on disc test using a 250 m distance, 150 rpm and 20 N load. 100Cr6 steel was selected as the counterface material during the wear tests. The results showed that titanium alloy with a content of 10 wt.% Mo has the highest wear resistance within the Ti– x Mo alloys. In addition, Ti–10Mo alloys showed an intensive wear resistance compared to the Ti6Al4V alloy.